A look into hemostatic characteristics during pediatric liver transplantation using the thromboelastometry (ROTEM®) test. Issue 10 (9th May 2022) - Cho, Jun‐Ki; Moon, Young‐Jin; Song, In‐Kyung; Kang, En‐Joo; Shin, Won‐Jung; Hwang, Gyu‐Sam
Abstract: There is a paucity of evidence about the coagulation profile regarding the complexity of children undergoing liver transplantation (LT). This study aimed to investigate intraoperative hemostatic changes during pediatric LT according to the etiology for LT and examine the ability of rotational thromboelastometry (ROTEM ®, TEM International GmbH, Munich, Germany) as a point‐of‐care monitoring method. We evaluated 106 patients aged 3 months to 17 years undergoing LT for acute liver failure (ALF) and chronic liver disease, which consists of patients with cholestatic disease, metabolic/genetic disease, and cancer. A total of 731 ROTEM ® measurements, including 301 ellagic acid to initiate clotting via the intrinsic pathway, 172 tissue factor to initiate the extrinsic clotting cascade (EXTEM), and 258 cytochalasin D to inhibit platelet activity reflecting fibrinogen (FIBTEM), were analyzed at predetermined time points (the preanhepatic, anhepatic, and postreperfusion phases). We simultaneously conducted conventional coagulation tests. In children with ALF, preanhepatic measurements of conventional coagulation tests and ROTEM ® showed a more hypocoagulable state than other diseases. During LT, the coagulation profile was deranged, with a prolonged clotting time and reduced clot firmness, changes that were more profound in the cholestatic disease group. Maximum clot firmness (MCF) on EXTEM and FIBTEM were well correlated with the platelet count and fibrinogen concentration ( r  = 0.830, p  < 0.001 and r  = 0.739, p  < 0.001, respectively). On the EXTEM, MCF with 30 mm predicted a platelet count <30, 000/mm 3 (area under the curve, 0.985), and 6 mm predicted a fibrinogen concentration <100 mg/dl on the FIBTEM (area under the curve, 0.876). However, the activated partial thromboplastin time and prothrombin time were significant but only weakly correlated with the clotting time on the ROTEM ® . In children undergoing LT, coagulation profiles depend on the etiology for LT. During LT, ROTEM ® parameters could help detect thrombocytopenia and hypofibrinogenemia and guide transfusion therapy as a point‐of‐care monitoring method.